Capturing the multiple benefits associated with nature‐based solutions: Lessons from a natural flood management project in the Cotswolds, UK. (22nd November 2018) - Short, Chris; Clarke, Lucy; Carnelli, Fabio; Uttley, Chris; Smith, Brian
Abstract: Following severe flooding in 2007, a decision was taken in 2012 to explore nature‐based solutions in 250‐km 2 river catchment in the southern Cotswolds in the United Kingdom. The project involves working with landowners to create in channel, riparian, field, and woodland structures aimed at attenuating high flows or increasing infiltration rates to reduce flood risk. After 3 years, it is clear that the threshold for effectiveness requires the implementation of measures throughout large areas of the upstream catchment. Early results suggest that social, as well as natural, capital has been enhanced through the project. What is clear is the beneficial role of working with multiple stakeholders to implement natural flood management on a catchment wide scale. In this sense, the project has adopted a comanagement approach that brings together the knowledge of hydrologists, ecologists, farmers, woodland owners, and the local community to implement locally agreed solutions within a broader project framework. This paper will outline the initial findings and the governance structure within a theoretical framework of comanagement and suggest how this type of framework is suitable for a range of nature‐based solutions across Europe. However, the challenge remains in capturing the multiple benefits that such projects offer as these are often missed through conventional approaches such as cost–benefit analysis. The paper concludes by presented along with a potential way forward for a proof of concept for nature‐based solutions.